2021
DOI: 10.1021/acs.jchemed.0c00528
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Guided Inquiry Classroom Activity to Investigate Effects of Chemistry on Physical Properties of Elastomers

Abstract: Typical organization of science and mathematics K12 education divides subjects into discrete courses. However, science and engineering are highly interdisciplinary fields. To better equip students to engage in the interdisciplinary nature of real-world STEM research and practice, projects can be used to highlight the interconnectivity of core subjects. Here, we present an exploratory, guided inquiry classroom research project. This work details student-led experiments combining physics and chemistry principles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Guided-inquiry strategies were incorporated as substantial research has shown its benefits. These pedagogical methods are student-centered and effective in increasing student learning, higher-order thinking, and cognitive reasoning. Studies comparing inquiry-based to traditional laboratory activities reveal increased academic achievement in students involved in the inquiry experience. , Furthermore, students undertaking inquiry-based activities demonstrate higher confidence in the laboratory and in conducting research. ,, In these studies, inquiry-based learning also improved students’ problem-solving abilities and sense of self-efficacy …”
Section: Background Informationmentioning
confidence: 92%
“…Guided-inquiry strategies were incorporated as substantial research has shown its benefits. These pedagogical methods are student-centered and effective in increasing student learning, higher-order thinking, and cognitive reasoning. Studies comparing inquiry-based to traditional laboratory activities reveal increased academic achievement in students involved in the inquiry experience. , Furthermore, students undertaking inquiry-based activities demonstrate higher confidence in the laboratory and in conducting research. ,, In these studies, inquiry-based learning also improved students’ problem-solving abilities and sense of self-efficacy …”
Section: Background Informationmentioning
confidence: 92%
“…Scientific literature documents several guided inquiry activities based mainly on experiments carried out involving upper-level high school students, for example, about elastomers or silica aerogels . Other guided inquiry-based activities have been realized in virtual environments .…”
Section: Introductionmentioning
confidence: 99%
“…Soft robotics has been seen as an emerging field for engaging young students in STEM activities [5 -7] The new, soft materials [8] and open-source designs make it an accessible field to young children [9]. Additionally, recent work has highlighted the opportunities for soft robotics to attract a diversity of students to participate [9,10].…”
Section: Figurementioning
confidence: 99%
“…The research team utilized the AEIOU Observational framework as previously implemented [8] (See Table 1).…”
Section: Observation Protocolmentioning
confidence: 99%
See 1 more Smart Citation